Objective analysis of language use in cognitive-behavioral therapy: associations with symptom change in adults with co-occurring substance use disorders and posttraumatic stress. Issue 2 (4th March 2021) - Jennings, Anthony N.; Soder, Heather E.; Wardle, Margaret C.; Schmitz, Joy M.; Vujanovic, Anka A.
ABSTRACT: Substance use disorders (SUD) commonly co-occur with posttraumatic stress disorder (PTSD) symptoms, and the comorbidity is prevalent and difficult-to-treat. Few studies have objectively analyzed language use in psychotherapy as a predictor of treatment outcomes. We conducted a secondary analysis of patient language use during cognitive-behavioral therapy (CBT) in a randomized clinical trial, comparing a novel, integrated CBT for PTSD/SUD with standard CBT for SUD. Participants included 37 treatment-seeking, predominantly African-American adults with SUD and at least four symptoms of PTSD. We analyzed transcripts of a single, matched session across both treatment conditions, using the Linguistic Inquiry and Word Count (LIWC) program. The program measures language use across multiple categories. Compared to standard CBT for SUD, patients in the novel, integrated CBT for PTSD/SUD used more negative emotion words, partially consistent with our hypothesis, but less positive emotion words. Further, exploratory analyses indicated an association between usage of cognitive processing words and clinician-observed reduction in PTSD symptoms, regardless of treatment condition. Our results suggest that language use during therapy may provide a window into mechanisms active in therapy.